Preparation method of composite porous carbon adsorbent with core-shell structure and adsorbent

CN122974285APending Publication Date: 2026-10-27TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611451403.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

而碳分子筛的孔径调控介于丙烷和丙烯的动力学直径之间,虽实现了精准筛分,但其狭窄的孔道环境也降低了丙烯的吸附速率

Benefits of technology

[0019](1)本发明中,外壳碳分子筛层是先在内核多孔炭表面聚合酚醛树脂聚合物碳材料中间体,再经炭化转化为筛分层,解决了采用气相沉积等常规方法制备复合炭材料存在可控性差、制备过程重现率低等问题,实现了纳米级均匀、连续、厚度可控的壳层构筑。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974285A_ABST
    Figure CN122974285A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of adsorbing materials, and particularly relates to a preparation method of a core-shell structure composite porous carbon adsorbent and the adsorbent, and the adsorbing material is applied to propane / propylene separation. The preparation method is to take glucose, resorcinol and furfural as raw materials, first prepare inner core porous carbon from the glucose, and then carbonize the inner core porous carbon and the resorcinol and the furfural under an inert atmosphere to obtain the core-shell structure composite porous carbon adsorbent. The core-shell structure composite porous carbon adsorbent prepared by the present application is applied to the field of propane / propylene separation, has very low co-adsorption capacity for propane while maintaining high propylene adsorption capacity, and is suitable for separation of propane and propylene gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorption material technology, and in particular relates to a method for preparing a core-shell structured composite porous carbon adsorbent and the adsorbent itself, wherein the adsorbent material is used for propane / propylene separation. Background Technology

[0002] Propylene is the second largest bulk chemical produced in the petrochemical industry and an indispensable key intermediate in the synthesis of various polymers. Its global annual production is projected to exceed 130 million metric tons by 2030. Most downstream applications require propylene to reach polymer-grade purity (>99.5%). However, propylene production processes such as naphtha steam cracking and gas oil catalytic cracking inevitably produce propane impurities as byproducts, and the crude cracking products cannot directly meet usage requirements. Currently, industrial propane / propylene separation still heavily relies on energy-intensive cryogenic distillation processes. Adsorption separation technology shows significant advantages, featuring high energy efficiency and mild operating conditions. However, propane and propylene have highly similar molecular structures, almost identical molecular sizes, and very similar physical properties, posing a significant challenge to their efficient separation.

[0003] Porous adsorbents (such as zeolites and metal-organic frameworks (MOFs)) have been widely used in propane / propylene separation research. Current separation strategies mainly include flexible gate effect, thermodynamic equilibrium separation, molecular sieving, and kinetic diffusion differences. Among these, molecular sieving is considered the most promising and efficient strategy. By precisely controlling the pore size or channel geometry, propane can be excluded, thereby preventing its co-adsorption and achieving the preparation of high-purity propylene. However, due to the extremely small difference in kinetic diameter between propane and propylene, most sieving materials have low adsorption capacity and slow adsorption rate for propylene. Recent advances in the field of MOFs indicate that introducing local sieving channels can partially overcome this limitation. However, MOFs generally have limitations in terms of cost, stability, and large-scale synthesis, which restricts their application in industrial fields. Therefore, developing high-performance adsorbents that meet industrial needs remains a crucial goal.

[0004] Porous carbon materials are popular adsorbents in industry due to their large specific surface area, good stability, and low cost. Because of these excellent properties, microporous carbon based on various precursor sources has broad application prospects in gas separation. However, the separation of propane / propylene using porous carbon materials mostly relies on pore channel control to achieve thermodynamic equilibrium. For example, Chinese patent CN 114684808 A introduces reducing or oxidizing gases during carbonization to participate in the thermal condensation and growth and stacking of graphite microcrystals in the carbon precursor, forming uniform micropore sizes (0.45-0.6 nm), with an adsorption capacity of 1.23-8.54 mmol / g for propylene and 1.02-4.26 mmol / g for propane. While carbon molecular sieves achieve precise sieving by controlling the pore size between the kinetic diameters of propane and propylene, their narrow pore environment also reduces the adsorption rate of propylene. Therefore, it is difficult to balance adsorption performance and adsorption rate for porous carbon adsorbents. Furthermore, for porous carbon materials, due to the extremely high carbon content (>90%), there is a lack of functional groups and active sites for modification, making the controllable preparation of composite carbon materials particularly difficult. Summary of the Invention

[0005] In view of the above-mentioned problems existing in the prior art, the first objective of the present invention is to provide a method for preparing a composite porous carbon adsorbent with a core-shell structure. The composite porous carbon adsorbent prepared by this method has a core-shell structure, in which the core has a large pore size and pore volume, serving as an adsorption and storage region for propylene gas; the outer shell has a smaller pore size, allowing propylene to diffuse while effectively blocking propane, and the extremely thin shell thickness reduces the diffusion path of propylene, greatly improving the adsorption rate and adsorption efficiency of propylene.

[0006] The core-shell structured composite porous carbon adsorbent of the present invention is prepared by the following method:

[0007] (1) The glucose aqueous solution was reacted in a hydrothermal reactor for a period of time, and the hydrothermal product obtained after filtration, washing and drying was carbonized under an inert atmosphere to obtain porous carbon with a core.

[0008] (2) The core porous carbon is placed in an ethanol solution containing phenolic and aldehyde substances, heated and stirred to react, and a carbon material intermediate with a certain amount of phenolic resin polymer deposited on the surface of the core porous carbon is obtained.

[0009] (3) The carbon material intermediate is transferred to a tube furnace and carbonized in an inert atmosphere to obtain the core-shell structured composite porous carbon adsorbent.

[0010] Furthermore, in step (1), the mass concentration of the glucose aqueous solution is 0.4~0.6 g / mL.

[0011] Further, the phenolic substance mentioned in step (2) is any one of phenol, resorcinol, and pyrogallol; the aldehyde substance is any one of formaldehyde, furfural, and terephthalaldehyde.

[0012] Furthermore, the molar ratio of the phenolic substance to the aldehyde substance is 1:2.

[0013] Furthermore, in step (2), the reaction temperature is 60~80℃ and the heating and stirring time is 0.5~36 h.

[0014] Furthermore, the carbonization temperature in both step (1) and step (3) is 400℃~1000℃, and the carbonization time is 0.5~2 h.

[0015] In the preparation method mentioned in this invention, the precursor of the core porous carbon material is hydrothermal carbon synthesized from glucose via hydrothermal treatment. After hydrothermal treatment, the interior of the carbon molecules is filled with a large number of oxygen-containing functional groups, resulting in abundant oxygen content. These abundant oxygen elements escape in gaseous form during carbonization, etching the carbon framework structure and creating defects, thus forming abundant pores and increasing the specific surface area of ​​the composite carbon material. This is highly beneficial for the adsorption of propylene and propane. To filter out the co-adsorption of propane, this invention introduces a shell carbon molecular sieve layer on top of the core porous carbon material. Furthermore, by controlling the time the core porous carbon is immersed in an ethanol solution containing phenols and aldehydes, the thickness of the sieve layer is controllable, successfully preparing a core-shell composite porous carbon adsorbent with different shell thicknesses between 2 and 15 nm. This controllable sieve layer thickness effectively repels propane adsorption and significantly alleviates the diffusion resistance of propylene, thereby increasing the propylene adsorption rate.

[0016] A second objective of this invention is to provide a composite porous carbon adsorbent prepared by any of the above methods. The composite porous carbon adsorbent has a core-shell structure, with a shell thickness between 2 and 15 nm, and the core pore size distribution has two distinct concentrated pore size distribution locations, namely 0.36-0.39 nm and 0.48-0.52 nm.

[0017] A third objective of this invention is to provide the application of the aforementioned composite porous carbon material in propane / propylene separation processes or scenarios. A preferred embodiment is that, under conditions of 298 K and 1 bar, the equilibrium adsorption capacity for propylene is 42.4-56 cm⁻¹. 3 / g, the equilibrium adsorption capacity of propane is 0.12-0.45 cm⁻¹. 3 / g, achieving sieving and separation.

[0018] The present invention has the following beneficial effects:

[0019] (1) In this invention, the outer shell carbon molecular sieve layer is first polymerized on the surface of the porous carbon core to form a phenolic resin polymer carbon material intermediate, and then carbonized to form a sieve layer. This solves the problems of poor controllability and low reproducibility of the preparation process in the preparation of composite carbon materials by conventional methods such as vapor deposition, and realizes the construction of a uniform, continuous, and thickness-controllable shell layer at the nanoscale.

[0020] (2) Traditional porous carbon adsorbents often have to make trade-offs between adsorption capacity and sieving selectivity in propane / propylene separation. The adsorbent of the present invention achieves a synergistic effect of "high adsorption capacity - high selectivity - fast adsorption rate" by constructing a core-shell functional partition structure. The outer shell functions to sieve propane / propylene, while the inner core functions to transfer and store propylene. This core-shell composite structure enables the adsorbent of the present invention to maintain a high propylene adsorption capacity while reducing the co-adsorption of propane to an extremely low level, achieving a technical effect that is difficult to achieve with the traditional single-channel control strategy of carbon materials.

[0021] (3) The sieving channels of traditional carbon molecular sieves extend throughout the entire particle, requiring propylene molecules to diffuse through narrow channels across the entire particle size, resulting in high mass transfer resistance and slow adsorption rate. The composite porous carbon adsorbent provided by this invention utilizes an extremely thin outer shell for sieving. Propylene molecules diffuse and are stored rapidly through the 2-15 nm thick shell, entering the larger pores of the core (0.48-0.52 nm). This mass transfer structure significantly shortens the effective diffusion path of propylene and substantially increases the effective diffusion coefficient. Therefore, the composite porous carbon adsorbent of this invention maintains high selectivity while exhibiting an adsorption rate far superior to traditional homogeneous carbon molecular sieves, making it more suitable for rapid cyclic operation in actual pressure swing adsorption or temperature swing adsorption processes. Attached Figure Description

[0022] Figure 1 This is a TEM image of the HC@RFC-0.5 adsorbent prepared in Example 1.

[0023] Figure 2 This is a TEM image of the HC@RFC-6 adsorbent prepared in Example 2.

[0024] Figure 3 This is a TEM image of the HC@RFC-12 adsorbent prepared in Example 3.

[0025] Figure 4 The image shows the pore size distribution of the composite porous carbon adsorbents prepared in Examples 1, 2, and 3.

[0026] Figure 5 The images show the adsorption isotherms of propane and propylene for the composite porous carbon adsorbents prepared in Examples 1, 2, and 3.

[0027] Figure 6Small-angle X-ray scattering (SAXS) images of the composite porous carbon adsorbents prepared in Examples 1 and 2.

[0028] Figure 7 The adsorption isotherms of propane and propylene for the HC@RFC-36 adsorbent prepared in Example 4 are shown.

[0029] Figure 8 The adsorption isotherms of propane and propylene for the HC@RFC-3 adsorbent prepared in Example 5 are shown. Detailed Implementation

[0030] To better understand the technical content of this invention, the technical solution of this invention will be further described and explained below with reference to specific embodiments. The described embodiments are merely some embodiments of this invention, and not all embodiments; based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0031] Example 1

[0032] (1) 8 g of glucose was placed in a beaker containing 20 ml of deionized water and stirred with a glass rod to dissolve it. The solution was then transferred to a 50 ml stainless steel hydrothermal reactor lined with polytetrafluoroethylene and placed in an oven at 200 °C for 24 h to obtain hydrothermal carbon. The hydrothermal carbon in the hydrothermal reactor was then filtered, washed, and dried before being placed in a tube furnace for carbonization under a nitrogen atmosphere. The tube furnace was set to a heating program of 5 °C / min to reach 1000 °C and held at 1000 °C for 1 h. After natural cooling, a porous carbon material with a core was obtained.

[0033] (2) The core porous carbon material is placed in an ethanol solution containing phenol and formaldehyde. Phenol and formaldehyde are polymerized on the surface of the core porous carbon material in a 60°C water bath. After 0.5 h of reaction, the material is filtered out of the phenol-formaldehyde polymerization reaction system and dried at room temperature to obtain a carbon material intermediate with phenol-formaldehyde resin polymer polymerized on the surface of the core porous carbon.

[0034] (3) The carbon material intermediate was transferred to a tube furnace and carbonized under a nitrogen atmosphere. The heating program of the tube furnace was set to 5 °C / min to reach 1000 °C, and held at 1000 °C for 1 h. After natural cooling, a composite porous carbon adsorbent was obtained, named HC@RFC-0.5.

[0035] Figure 1 The images show TEM images of the HC@RFC-0.5 adsorbent prepared in Example 1, where (a) is an overall morphological image of the individual under TEM observation, and (b) is a magnified image of its edge. It is clearly visible from the images that there is a shell structure at the edge of the porous carbon core, indicating that the adsorbent has a distinct core-shell structure.

[0036] Figure 4 The pore size distribution curves show that the composite porous carbon adsorbent prepared in Example 1 has two pore size distribution centers, namely 0.36 nm and 0.48 nm, which are hierarchical pore structures.

[0037] Figure 5 The adsorption isotherm curves of propane and propylene prepared by the composite porous carbon adsorbent show that the equilibrium adsorption capacity of propane prepared by the method of this invention is 0.12 cm⁻¹. 3 / g, the equilibrium adsorption capacity of propylene is 53 cm⁻¹. 3 / g.

[0038] Example 2

[0039] (1) 10 g of glucose was placed in a beaker containing 20 ml of deionized water and stirred with a glass rod to dissolve it. The solution was then transferred to a 50 ml stainless steel hydrothermal reactor lined with polytetrafluoroethylene and placed in an oven at 200 °C for 24 h to obtain hydrothermal carbon. The hydrothermal carbon in the hydrothermal reactor was then filtered, washed, and dried before being placed in a tube furnace for carbonization under a nitrogen atmosphere. The tube furnace was set to a heating program of 5 °C / min to reach 1000 °C and held at 1000 °C for 1.5 h. After natural cooling, a porous carbon material with a core was obtained.

[0040] (2) The core porous carbon material is placed in an ethanol solution containing resorcinol and furfural. The resorcinol and furfural are polymerized on the surface of the core porous carbon material in a 60°C water bath. After 6 hours of reaction, the material is filtered out of the phenolic polymerization reaction system and dried at room temperature to obtain a carbon material intermediate with phenolic resin polymer polymerized on the surface of the core porous carbon.

[0041] (3) The carbon material intermediate was transferred to a tube furnace and carbonized under a nitrogen atmosphere. The heating program of the tube furnace was set to 5 °C / min to reach 1000 °C, and held at 1000 °C for 1.5 h. After natural cooling, a composite porous carbon adsorbent was obtained, named HC@RFC-6.

[0042] observe Figure 2 The TEM images, including the overall morphology of the individual (a) and the magnified edge view (b), show that the coating layer on the outer surface of the core porous carbon is clearly visible, which further confirms that the composite porous carbon adsorbent prepared in Example 2 has a distinct core-shell structure.

[0043] Figure 4 The pore size distribution curves show that the composite porous carbon adsorbent prepared in Example 2 has two pore size distribution centers, which are 0.38 nm and 0.51 nm, respectively, and is a hierarchical pore structure.

[0044] Figure 5 The adsorption isotherm curves of propane and propylene prepared by the composite porous carbon adsorbent show that the equilibrium adsorption capacity of propane prepared in this embodiment is 0.15 cm⁻¹. 3 / g, the equilibrium adsorption capacity of propylene is 48 cm⁻¹. 3 / g.

[0045] Figure 6 The small-angle X-ray scattering pattern shows that the HC@RFC-6 adsorbent prepared in Example 2 has a clear halo on its outer ring and a more obvious core-shell structure compared to the HC@RFC-0.5 adsorbent prepared in Example 1. This indicates that as the porous carbon material in the core is treated in the phenolic solution for a longer time, multiple layers of phenolic resin polymers are polymerized on the surface of the core, resulting in a significant increase in the thickness of the shell layer. In other words, the thickness of the outer sieve layer (i.e., the shell layer) can be controlled and adjusted.

[0046] Example 3

[0047] (1) 12 g of glucose was placed in a beaker containing 20 ml of deionized water and stirred with a glass rod to dissolve it. The solution was then transferred to a 50 ml stainless steel hydrothermal reactor lined with polytetrafluoroethylene and placed in an oven at 200 °C for 24 h to obtain hydrothermal carbon. The hydrothermal carbon in the hydrothermal reactor was then filtered, washed, and dried before being placed in a tube furnace for carbonization under a nitrogen atmosphere. The tube furnace was set to a heating program of 5 °C / min to reach 1000 °C and held at 1000 °C for 2 h. After natural cooling, a porous carbon material with a core was obtained.

[0048] (2) The core porous carbon material is placed in an ethanol solution containing pyrogallol and furfural. The pyrogallol and furfural are polymerized on the surface of the core porous carbon material in a water bath at 60°C. After 12 h of reaction, the mixture is filtered, the core porous carbon material is removed from the phenolic polymerization reaction system and dried at room temperature to obtain a carbon material intermediate with phenolic resin polymer polymerized on the surface of the core porous carbon.

[0049] (3) The carbon material intermediate was transferred to a tube furnace and carbonized under a nitrogen atmosphere. The heating program of the tube furnace was set to 5 °C / min to reach 1000 °C, and held at 1000 °C for 2 h. After natural cooling, a composite porous carbon adsorbent was obtained. It was named HC@RFC-12.

[0050] exist Figure 3 In the TEM images, it can be seen from the overall morphology (a) and the magnified edge (b) of the individual that as the treatment time of the core porous carbon material in the phenolic solution continues to increase, the thickness of its outer shell will further increase.

[0051] Figure 4The pore size distribution curves show that the composite porous carbon adsorbent prepared in Example 3 has two pore size distribution centers, which are 0.39 nm and 0.52 nm, respectively, and is a hierarchical pore structure.

[0052] Figure 5 The adsorption isotherm curves of propane and propylene prepared by the composite porous carbon adsorbent show that the equilibrium adsorption capacity of propane prepared in this embodiment is 0.16 cm⁻¹. 3 / g, the equilibrium adsorption capacity of propylene is 42.4 cm⁻¹. 3 / g.

[0053] contrast Figure 1 , 2 TEM images of the composite porous carbon adsorbents in Examples 1, 2, and 3 of Part 3 clearly show that the outer shell of the HC@RFC-0.5 adsorbent (Example 1) is uniformly thick and consists of a narrow shell layer. However, as the treatment time of the core porous carbon material in the phenolic solution increases, the shell layers of the HC@RFC-6 adsorbent (Example 2) and HC@RFC-12 adsorbent (Example 3) become significantly coarser and uneven, exhibiting local protrusions. These results demonstrate that the preparation method of the core-shell structured composite porous carbon adsorbent of the present invention is reliable, and the thickness of the outer shell layer of the composite porous carbon adsorbent can be adjusted simply by controlling the preparation time. Therefore, the preparation method of the composite porous carbon adsorbent of the present invention, by precisely controlling the composite time (i.e., controlling the time of the core porous carbon in an ethanol solution containing phenols and aldehydes), continuously optimizes the thickness of the sieved shell layer, resulting in an adsorbent that can shorten the diffusion distance of propylene in the sieved layer and reduce diffusion resistance.

[0054] Example 4

[0055] (1) 9 g of glucose was placed in a beaker containing 20 ml of deionized water and stirred with a glass rod to dissolve it. The solution was then transferred to a 50 ml stainless steel hydrothermal reactor lined with polytetrafluoroethylene and placed in an oven at 200 °C for 24 h to obtain hydrothermal carbon. The hydrothermal carbon in the hydrothermal reactor was then filtered, washed, and dried before being placed in a tube furnace for carbonization under a nitrogen atmosphere. The tube furnace was set to a heating program of 5 °C / min to reach 1000 °C and held at 1000 °C for 2 h. After natural cooling, a porous carbon material with a core was obtained.

[0056] (2) The core porous carbon material was placed in an ethanol solution containing resorcinol and formaldehyde. The resorcinol and formaldehyde were polymerized on the surface of the core porous carbon material in a water bath at 60°C. After 36 h of reaction, the material was filtered out of the phenol-formaldehyde polymerization reaction system and dried at room temperature to obtain a carbon material intermediate with phenol-formaldehyde resin polymer polymerized on the surface of the core porous carbon.

[0057] (3) The carbon material intermediate was transferred to a tube furnace and carbonized under a nitrogen atmosphere. The heating program of the tube furnace was set to 5 °C / min to reach 1000 °C, and held at 1000 °C for 2 h. After natural cooling, a composite porous carbon adsorbent was obtained, named HC@RFC-36.

[0058] Figure 7 The equilibrium adsorption capacity of the HC@RFC-36 adsorbent prepared in this example for propylene is shown to be 56 cm⁻¹. 3 / g, the equilibrium adsorption capacity of propane is 0.13 cm⁻¹. 3 / g.

[0059] Example 5

[0060] (1) Dissolve 8 g of glucose in a beaker containing 20 ml of deionized water by stirring with a glass rod. Transfer the solution to a 50 ml stainless steel hydrothermal reactor lined with polytetrafluoroethylene (PTFE), and place it in a 200 °C oven for 24 h to obtain hydrothermal carbon. Then, filter, wash, and dry the hydrothermal carbon in the hydrothermal reactor, and place it in a tube furnace for carbonization under a nitrogen atmosphere. The tube furnace is set to a heating program of 5 °C / min to reach 1000 °C, and then held at 1000 °C for 2 h. After natural cooling, a porous carbon material with a core is obtained.

[0061] (2) The core porous carbon material was placed in an ethanol solution containing resorcinol and terephthalaldehyde. The resorcinol and terephthalaldehyde were polymerized on the surface of the core porous carbon material in a water bath at 60°C. After 3 h of reaction, the mixture was filtered, and the core porous carbon material was removed from the phenolic polymerization reaction system and dried at room temperature to obtain a carbon material intermediate with phenolic resin polymer polymerized on the surface of the core porous carbon.

[0062] (3) The carbon material intermediate was transferred to a tube furnace and carbonized under a nitrogen atmosphere. The heating program of the tube furnace was set to 5 °C / min to reach 1000 °C, and held at 1000 °C for 2 h. After natural cooling, a composite porous carbon adsorbent was obtained. It was named HC@RFC-3.

[0063] Figure 8 The equilibrium adsorption capacity of the HC@RFC-3 adsorbent prepared in this embodiment for propylene is shown to be 52 cm⁻¹. 3 / g, the equilibrium adsorption capacity of propane is 0.45 cm⁻¹. 3 / g.

[0064] Although the present invention has been described in detail above with general descriptions, specific embodiments, and experiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a core-shell structured composite porous carbon adsorbent, characterized in that, Includes the following steps: (1) The glucose aqueous solution was reacted in a hydrothermal reactor for a period of time, and the hydrothermal product obtained after filtration, washing and drying was carbonized under an inert atmosphere to obtain porous carbon with a core. (2) The core porous carbon is placed in an ethanol solution containing phenolic and aldehyde substances, heated and stirred to react, and a carbon material intermediate with a certain amount of phenolic resin polymer polymerized on the surface of the core porous carbon is obtained. (3) The carbon material intermediate is transferred to a tube furnace and carbonized in an inert atmosphere to obtain the core-shell structured composite porous carbon adsorbent.

2. The preparation method according to claim 1, characterized in that, In step (1), the mass concentration of the glucose aqueous solution is 0.4~0.6 g / mL.

3. The preparation method according to claim 1, characterized in that, The phenolic substance mentioned in step (2) is any one of phenol, resorcinol, and pyrogallol; the aldehyde substance is any one of formaldehyde, furfural, and terephthalaldehyde.

4. The preparation method according to claim 1 or 3, characterized in that, The molar ratio of the phenolic substance to the aldehyde substance is 1:

2.

5. The preparation method according to claim 1, characterized in that, In step (2), the reaction temperature is 60~80℃ and the heating and stirring time is 0.5~36 h.

6. The preparation method according to claim 1, characterized in that, The carbonization temperature in both step (1) and step (3) is 400℃~1000℃, and the carbonization time is 0.5~2 h.

7. A composite porous carbon adsorbent prepared by any one of the preparation methods described in claims 1, 2, 3, 5, and 6.

8. The composite porous carbon adsorbent according to claim 7, characterized in that, The composite porous carbon adsorbent has a core-shell structure with a shell thickness of 2-15 nm. Its pore size distribution has a hierarchical distribution with two distribution centers at 0.36-0.39 nm and 0.48-0.52 nm.

9. The composite porous carbon adsorbent of claim 7, wherein the prepared microporous activated carbon is used for the adsorption and separation of propane / propylene.

10. The composite porous carbon adsorbent according to claim 7, characterized in that, Under conditions of 298 K and 1 bar, the equilibrium adsorption capacity of the composite porous carbon adsorbent for propane is 0.12~0.45 cm⁻¹. 3 / g, the equilibrium adsorption capacity for propylene is 42.4~56 cm⁻¹. 3 / g.

Citation Information

Patent Citations

  • Preparation method of porous nano carbon material and application of porous nano carbon material in separation of propylene / propane

    CN114684808A